Kramer vs. Kramer ([s.l.] Columbia Pictures, 1979)
Kramer vs. Kramer is a story of contemporary relationships, values, and choices. Returning home late from work one night, a career obsessed Ted Kramer (Hoffman) is told by his wife, Joanna (Sreep), that she is leaving him. After a lifetime of being 'somedody's daughter or somebody's wife' she is going of to find herself-leaving Ted to care for their six-year old son. Ted, while trying to hold down his job, gets to really know his son as few fathers do, cooking his meals, taking him to the park, understanding every need and fear. For the first time in his life he feels like a fulfilled parent. But then Joanna returns. and she wants her son back.
VCD
Based upon the novel by Avery Corman ; produced by Stanley R. Jaffe ; written and directed by Robert Benton.
Dustin Hoffman, Meryl Streep, Justin Henry
Keywords: Family in the motion pictures; Husband and wife; Feature films